The effects of personal and organizational resources on work outcomes of expatriate academics - Sri Ramalu, Subramaniam; Subramaniam, Chandrakantan; Nadarajah, Gunalan (2017)
Internationalization of higher education has created job opportunities for expatriate academics to explore international experience in many countries around the world.This has been case in Malaysia as well. With the aspiration to become regional educational hub by 2020, Malaysian universities have been actively recruiting foreign faculties as part of its internationalization strategy.This phenomena has posed greater challenge to human resource management of the respective universities.Drawing from job resources model and self-determination theory, this study aims to examine the effects of personal and organizational resources on the expatriate academics’ work outcomes.Effective expatriate academics will significantly contribute to the excellence of the universities in providing world-class education to its customers hence understanding the determinant factors of their work outcomes is imperative.A survey-based quantitative research using a sample of 152 expatriate academics employed in 20 Malaysian public universities revealed some important findings. Both the personal (cultural intelligence) and organizational resources (perceived organizational support) are found to be important determinants of expatriate academics’ work engagement and psychological needs satisfaction.The findings suggest that higher level of cultural intelligence and perceived organizational support may lead to greater work engagement and psychological needs satisfaction among expatriate academics. Few theoretical and practical implications can be concluded from this study especially in relation to international human resource management.